Analysis of Influencing Factors Intention to Use E-Wallet Using Tam Model - Siregar, Ifan Wicaksana; Yulianti, Eka; Susyani, Novi (Budapest International Research and Critics University, 2022)
This study aims to determine the factors that influence the intention to use e-wallets in Indonesia. The study has narrowed the knowledge gap of previous studies in terms of examining four factors ina single setting and focusing on vulnerable 18-55year olds as respondents. In addition, this research has developed mainstream literature on the use of e-wallets. The findings ascertained the significance of the four factors under investigation, and three hypotheses supported for respondents, allowing implications from multiple perspectives of the strategy to suggest increased use of e-money. According to the findings in this study, trust in the provider, the value of enjoyment and the value of comfort seem to be important factors that will influence the intention to use an e-wallet, thus requires more attention from online transaction facility providers, banks, and software developers. This means that whatever improvement of the existing e-payment system must consider these characteristics, namely: comfortable, enjoyable and trustworthy.